Answer :

Let ‘a’ be the first term and ‘d’ be the common difference

Sn= 3n2 + 6n


Firsdt term, a, S1 = 3(1)2 + 6(1)


= 3 + 6 = 9


S2 = 3(2)2 + 6(2)


a + a + d = 12 + 12


9 + 9 + d = 24


18 + d = 24


d = 6


Therefore, an = a + (n – 1) d


= 9 + (n – 1) 6


= 6n + 3


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Arithmetic Progression- Don't miss these QuestionsArithmetic Progression- Don't miss these QuestionsArithmetic Progression- Don't miss these Questions56 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses